EFEKTIVITAS PROGRAM DANA HIBAH PARIWISATA BAGI INDUSTRI PARIWISATA DI KABUPATEN BADUNG PADA MASA PANDEMI COVID-19 - Putu Delvia Noviana Dewi; Ni Made Tirtawati; Ida Bagus Putra Negarayana (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
The decline in the number of foreign tourist arrivals due to the Covid-19 pandemic has put considerable pressure on the tourism industry. Therefore, the tourism grant program is structured as an effort to restore the tourism sector for the tourism industry (hotels and restaurants). This research aims to; identify obstacles in the stages of implementing the grant program in Badung Regency and analyze the effectiveness of the tourism grant program for restaurants in Badung Regency. The data analysis technique used is descriptive qualitative supported by quantitative with a measuring instrument, namely weighted average analysis. The results of this study indicate that obstacles are found at each stage of the implementation of the tourism grant program, both from the implementing team and the restaurant business side. Meanwhile, the effectiveness ratio of the tourism grant program for restaurant businesses shows a percentage of 74.4% with an achievement level of